Osmotic diuresis in chronic kidney disease: its significance and clinical utility (2019)
Introduction The kidneys contribute to maintain plasma osmolality in normal range by achieving the adequate daily osmolar urine excretion (DOUE). An equation has been described for estimating the expected daily urine volume necessary to excrete the osmolar load required to keep serum osmolality in normal range. According to this equation, a difference between real and expected daily osmolar diuresis (DOD) can be obtained, being normally this difference value zero (± 500 cc). However, a positive DOD difference signifies a reduced urine concentration capability, while a negative DOD difference signifies a reduced urine dilution capability. Therefore, we decided to originally investigate how DOUE, and DOD difference are modified through the different stages of CKD. Materials and methods 61 patients suffering from CKD (stages I–V) secondary to glomerulopathies were studied. Creatinine clearance (CrCl), DOUE, and difference between real and expected DOD were obtained from each patient. Besides, correlation (Spearman) between CrCl and DOUE, and between CrCl and real–expected DOD difference were also obtained. Results Spearman correlation between CrCl and DOUE was positive and significant (Spearman’s ρ = 0.63, p < 0.0001). In addition, CKD patients who were not able to achieve the minimal DOUE required (600 mOsm/day) were mostly those with CrCl < 40 mL/min. Spearman correlation between CrCl and real–expected DOD difference was negative and significant (Spearman’s ρ = − 0.4, p < 0.0013). Additionally, abnormal DOD difference (> 500 cc) was found in CKD patients with CrCl < 80 mL/min/1.73 m2. Conclusion Daily osmolar urine excretion, and difference between real and expected daily osmolar diuresis are simple and significant clinical parameter which can be useful to easily evaluate urine concentration–dilution capability (tubular function) in CKD patients.